Transformation and anti-racism in policy and practice at an elite private school: a case study of the experiences of recently graduated black students - Khanyile, Sandisiwe (School of Education, 2024)
The South African Schools Act of 1996 catalysed by the Bill of Rights and the South African Constitution, formalised the desegregation of schools in South Africa, and created the opportunity for students from diverse cultural backgrounds to attend schools of their choice (Vandeyar, 2008:p. 287). Although the above policies set the stage for desegregation to unfold at schools, they not did not further interrogate the quality of contact in the personal attitudes of the students and teachers, as well as in the institutional arrangements, ethos, and policies of the schools (Vandeyar, 2008). Vandeyar (2008: p. 287), argues that “instead of becoming models of societal integration, schools have continued to reflect the hegemonic dominance of whiteness and as a result racism has continued unabated”. Framed by theories of Coloniality/Decoloniality, Critical Race Theory and Raciolinguistic ideologies, this qualitative case-study investigated the existing transformation and antiracism policies at an elite private school. It also explored the racialised experiences of five learners of colour as well as how they experienced the implementation of the policies. Five former pupils from the selected school were interviewed, as well as one current parent and former member of the Transformation Committee at the school. The research findings suggest that the existing policies and the implementation thereof are insufficient to address continuing racist and discriminatory practices. Furthermore, learners reported a lack of action on the school's part in response to racist incidents. Additionally, learners expressed feeling that they needed to assimilate in order to fit into the culture of the school.